HLA-targeted sequencing reveals the pathogenic role of HLA-B*15:02/HLA-B*13:01 in albendazole-induced liver failure: a case report and a review of the literature - Liao, Jin-Mao; Zhan, Yan; Zhang, Zheng; Cui, Jia-Jia; Yin, Ji-Ye (Frontiers in Pharmacology, 2023)
Drug-induced liver injury (DILI) is one of the serious adverse drug reactions (ADRs), which belongs to immune-mediated adverse drug reactions (IM-ADRs). As an essential health drug, albendazole has rarely been reported to cause serious liver damage. A young man in his 30s developed severe jaundice, abnormal transaminases, and poor blood coagulation mechanism after taking albendazole, and eventually developed into severe liver failure. The patient was found heterozygous of HLA-B*15:02 and HLA-B*13:01 through HLA-targeted sequencing, which may have a pathogenic role in the disease. This case report summarizes his presentation, treatment, and prognosis. A useful summary of the diagnosis and associated genetic variant information is provided.